2020
DOI: 10.1002/dmrr.3290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on immature platelet fraction and its association with coronary artery disease

Abstract: Background: Higher prothrombotic status and alterations in platelet function and thrombopoiesis are associated with diabetes mellitus (DM). We assessed the impact of diabetes and glucose control on the immature platelet fraction (IPF) and their relationship with prevalence and extent of coronary artery disease (CAD).Methods: Consecutive patients undergoing coronary angiography were included.Significant CAD was defined as at least one vessel stenosis greater than 50%. IPF levels were measured at admission by ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several subanalyses of this study showed no association of levels of RPs with concomitant antiplatelet therapy, use of statins, age or gender [49,50]. Only in the subgroup of patients with CAD and diabetes mellitus were high levels of RPs associated with a lower prevalence of CAD [51], but with a higher incidence of major adverse cardiovascular events and a lower incidence of bleeding [52]. Several studies comparing healthy subjects, patients with stable CAD and patients with ACS showed significant elevated levels of RPs in patients with ACS, especially in patients with STEMI [39,53,54].…”
Section: Immature Platelets and Cardiovascular Diseasementioning
confidence: 76%
“…Several subanalyses of this study showed no association of levels of RPs with concomitant antiplatelet therapy, use of statins, age or gender [49,50]. Only in the subgroup of patients with CAD and diabetes mellitus were high levels of RPs associated with a lower prevalence of CAD [51], but with a higher incidence of major adverse cardiovascular events and a lower incidence of bleeding [52]. Several studies comparing healthy subjects, patients with stable CAD and patients with ACS showed significant elevated levels of RPs in patients with ACS, especially in patients with STEMI [39,53,54].…”
Section: Immature Platelets and Cardiovascular Diseasementioning
confidence: 76%
“…62 Nevertheless, also negative studies without any association between RPs and diabetes exist. 70,71 Reasons for contrasting results could be because of different measurement techniques to assess RPs and the implementation of heterogeneous patient populations.…”
Section: Rps In High Risk and Diseased Populationmentioning
confidence: 99%